Biomechanical strategies to reach a compromise between stiffness and flexibility in hind femora of desert locusts. (15th October 2021) - Li, Chuchu; Gorb, Stanislav N.; Rajabi, Hamed
Abstract: Insect cuticle can reach a wide range of material properties, which is thought to be the result of adaptations to applied mechanical stresses. Biomechanical mechanisms behind these property variations remain largely unknown. To fill this gap, here we performed a comprehensive study by simultaneous investigation of the microstructure, sclerotization and the elasticity modulus of the specialized cuticle of the femora of desert locusts. We hypothesized that, considering their different roles in jumping, the femora of fore-, mid- and hind legs should be equipped with cuticles that have different mechanical properties. Surprisingly, our results showed that the hind femur, which typically bears higher stresses, has a lower elasticity modulus than the fore and mid femora in the longitudinal direction. This is likely due to the lower sclerotization and different microstructure of the hind femur cuticle. This allows for some deformability in the femur wall and is likely to reduce the risk of mechanical failure. In contrast to both other femora, the hind femur is also equipped with a set of sclerotized ridges that are likely to provide it with the required stiffness to withstand the mechanical loads during walking and jumping. This paper is one of only a few comprehensive studies on insect cuticle, which advances the current understanding of the relationship between the structure, material property and function in this complex biological composite. Statement of significance: Insect cuticle is a biological composite with strong anisotropy and wide ranges of material properties. Using an example of the femoral cuticle of desert locusts, we measured the elasticity modulus, microstructure and sclerotization level of the cuticle. Our results show that, although the hind femur withstands most of the stress during locomotion, it has a lower elasticity modulus than the fore and mid femora. This is likely to be a functional adaption to jumping, in order to allow small deformations of the femur wall and reduce the risk of material failure. Our results deepen the current understanding of the structure-material-function relationship in the complex insect cuticle. Graphical abstract: Image, graphical abstract